An Anatomy of Firm Level Job Creation Rates over the Business Cycle - Werner Hölzl; Peter Huber (Austrian Institute of Economic Research (WIFO), 2009)
We study the evolution and cyclical dependency of the cross sectional distribution of firm level job creation rates from 1975 to 2004 for the Austrian private sector. We find that the share of firms that o not adjust has declined over time, but that the share of entries, exits, growing and declining firms increased. The share of firms adjusting is higher in upswings than in downturns and the higher order moments of the job creation distribution follow distinct cyclical patterns. The smallest firms and firms at the extremes of the growth rate distribution are largely unaffected by the business cycle.
Keywords: 330; Employment Adjustment; Business Cycle; Firm growth; Konjunktur; Beschäftigungseffekt; Unternehmenserfolg; Privatwirtschaft; Österreich